Pengaruh Work Life Balance Dan Stress Kerja Terhadap Kepuasan Kerja Pegawai Di BPPLOP Kota Semarang - Daeni, Haerlis Mawar; Oemar, Moehammad Shadiq Helmy; Sofyanty, Devy (CV Warnak Johanna Nusantara, 2025)
Abstracts - This study aims to analyze the effect of Work Life Balance and Job Stress on employee Job Satisfaction at the Center for Student Sports Education and Training, both partially and simultaneously. The research employs a quantitative approach with statistical analysis. The data collected include both primary and secondary sources, using a questionnaire as the main instrument. The sampling technique used is non-probability sampling with a saturated sample approach, in which all 56 employees in the population were selected as respondents. Data analysis techniques include instrument testing, classical assumption testing, and hypothesis testing consisting of multiple linear regression analysis, F-test, t-test, and coefficient of determination. The data were processed using SPSS version 25. The results show that partially, Work Life Balance has a positive and significant effect on employee job satisfaction, while Job Stress has no significant effect. Simultaneously, both Work Life Balance and Job Stress have a positive and significant effect on employee Job Satisfaction at the Center for Student Sports Education and Training.